On polynomials generated by a four-term recurrence relation and linear coefficients - Botta, Vanessa [UNESP]; Filho, Eduardo Fornazieri [UNESP] (Springer Nature, 2023)
This paper treats the properties of polynomials generated by a four-term recurrence relation and linear coefficients. From the eigenvalue theory, we give information on the location of the zeros. Furthermore, we investigate the distribution and simplicity of the zeros in a particular case.
Keywords: Eigenvalue representation; Four-term recurrence relation; Polynomials; Zeros